The Eliminating Forced Marriage Through the Law: Effectiveness and Social Urgency - Bidayati, Kholis; Tuerxun, Abudushalamu; Baehaqi, Wawan (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
This article discusses the law's effectiveness and urgency in eliminating forced marriage in Indonesia. This research is qualitative research with a legal effectiveness approach. The primary data in this research is quantitative data from previous research that discussed the phenomenon of forced marriage. Secondary data consists of related laws and regulations, journals, and books. The research results show that legal regulations regarding the rejection of forced marriage have been regulated in various favorable laws in Indonesia but have not shown a significant influence in reducing the high rate of forced marriage. It is for two reasons. Firstly, there are still overlapping legal regulations regarding forced marriage, namely between the marriage dispensation article (UUP) and the article prohibiting child marriage (UU PKS). Second, the root of the problem of forced marriage lies in social factors, like a weak economy and a low level of public education.